(untitled) (Антропологический форум / Forum for Anthropology and Culture, 2021)
The review examines the new approaches to the study of museums which are the subject of The Politics of Affect. At the centre of attention is the very concept of ‘the museum’ and its various treatments by the authors of this collection, as are the various practices for producing emotion in exhibition spaces. The diversity of the contemporary forms of museum activity in Russia presented in the publication casts doubt on the thesis of a museum crisis expressed on the pages of the book. At the same time, the opening up of Russian museums to international discussion in the context of the ‘new museology’ is a very pressing task, important both for an understanding of the specifics of the Russian context in which museums exist, and for a resolution of global questions regarding the evolution and change of museums in the modern world.